Remediasi Kromium Heksavalen Melalui Bioaugmentasi Konsorsium Bakteri Indigenous Wilayah Tercemar Limbah Cair Sablon dengan Biostimulasi Bulu Ayam Broiler - Made Luhur Sahadeva (Jurnal Pendidikan Biologi Undiksha, 2024)
Hexavalent chromium or Cr (VI) is a heavy metal that is dangerous to living things if it enters the body's metabolism because of its high permeability and oxidation ability which can disrupt biological systems. Cr (VI) is found in large quantities in textile dyes in the screen printing industry. The results of washing screen printing produce Cr (VI) waste which is dangerous to the environment. The waters that are the place where the waste from washing screen printing flows become polluted and toxic due to waste that is not treated first. One way to overcome this pollution is by bioremediation. In this research, bioremediation was carried out using a consortium of indigenous bacteria with biostimulation of broiler chicken feathers. The bacterial consortium was taken from sediments of waters contaminated with Cr (VI) waste, then isolated and tested for tolerance to chromium. The bacterial consortium that is resistant to chromium was then used for bioremediation by a combination of bioaugmentation and biostimulation using broiler chicken feathers as a nutrient supply for the bacteria. This research aims to obtain a bacterial consortium with the highest effectiveness of Cr (VI) remediation through a combination of biaugmentation and biostimulation of broiler chicken feathers. Base on results of isolation and tolerance tests show that indigenous bacteria from polluted areas have the ability to survive and grow even in conditions contaminated with chromium. However, the addition of nutrients from broiler chicken feather meal as a carbon and nitrogen source did not succeed in increasing the metabolic activity of bacteria in degrading Cr(VI). The results of the ANOVA one way test also support the conclusion that there is no significant difference in effectiveness between treatments with varying concentrations of chicken feather flour. Bacterial consortia have not been able to improve Cr (VI) remediation due to nutritional incompatibility and difficulties in decomposing nutrients in chicken feathers, as well as the possibility of antagonistic interactions between microbial strains.